From Community Cancer to Common Entertainment: The Dynamics of Lottery Legalization in Massachusetts. Issue 1 (16th December 2016) - Wetzel, Christopher; Luciano, Kimberly
Abstract : To theorize the process by which behaviors once regarded as deviant become normalized, this article analyzes the legalization of a state‐run lottery in the American state of Massachusetts. Lotteries are an important case to study the dynamism of socially constructed problems as well as the creation of gaming markets because they raise moral, social, and economic concerns associated with all types of gaming with the added dimension of having the state government serving as regulator and proprietor of the wagering. Drawing on newspaper articles and archival records, this article examines mobilization around failed efforts to establish a lottery in Massachusetts in the 1930s and 1950s, followed by the successful legalization of a lottery in the 1970s. Highlighting meaning making collective struggles over the lottery in variable circumstances illuminates the processes by which the perceptions of proprietors of operations, patrons of the games, and the distribution of proceeds shift, ultimately turning what was once an illegal enterprise into a socially accepted state institution.